Relationship of plasma cell‐free DNA level with mortality and prognosis in patients with Crimean–Congo hemorrhagic fever. Issue 7 (5th January 2016) - Bakir, Mehmet; Engin, Aynur; Kuskucu, Mert Ahmet; Bakir, Sevtap; Gündag, Omür; Midilli, Kenan
Abstract : Crimean–Congo hemorrhagic fever (CCHF) is a viral infection. Circulating plasma cell‐free DNA (pcf‐DNA) is a novel marker indicating cellular damage. So far, the role of pcf‐DNA did not investigate in CCHF patients. In the current study, pcf‐DNA levels were investigated in CCHF patients with different clinical severity grades to explore the relationship between circulating pcf‐DNA level, virus load, and disease severity. Seventy‐two patients were categorized as mild, intermediate, and severe based on severity grading scores. The pcf‐DNA level was obtained from all participants on admission and from the survivors on the day of the discharge. The controls consisted of 31 healthy. Although the pcf‐DNA level at admission was higher in patients than in the controls, the difference was not statistically significant ( P  = 0.291). However, at admission and in the convalescent period, the difference between pcf‐DNA levels in mild, intermediate, and severe patient groups was significant. The pcf‐DNA level in severe patients was higher than in the others. Furthermore, compared to survivors, non‐survivors had higher pcf‐DNA levels at admission ( P  = 0.001). A direct relationship was found between the pcf‐DNA level and the viral load on the day of discharge in surviving patients. ROC curve analysis identified a pcf‐DNA level of 0.42 as the optimal cut‐off for prediction of mortality. The positive predictive value, negative predictive value, specificity, and sensitivity for predicting mortality was 100%, 72%, 100%, and 79%, respectively. In summary, our findings revealed that pcf‐DNA levels may be used as a biomarker in predicting CHHF prognosis. J. Med. Virol. 88:1152–1158, 2016 . © 2015 Wiley Periodicals, Inc.